A Conversation with Linda Hutcheon on Film Adaptation - Pascal, Marie (Transcr(é)ation, 2022)
Linda Hutcheon is a pioneer on cinema adaptation, with her book A Theory of Adaptation (2006), where she envisions adaptation as a transmedial process rather than as a faithful relationship a film must respect with a book. She has rejuvenated research in the field, overwhelmed dead-ends encountered by the adaptation critique, and offered thrilling perspectives on how to conceive such relationships between medias as different as comics, novels, drama, opera, video games, etc. Although her research interests now shifted to the operatic genre, she was as kind as to answer my questions for this first dossier of Transcr(é)ation.